2019
DOI: 10.1080/15592294.2019.1581590
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic activation of POTE genes in ovarian cancer

Abstract: The POTE gene family consists of 14 homologous genes localized to autosomal pericentromeres, and a subset of POTEs are cancer-testis antigen (CTA) genes. POTEs are over-expressed in epithelial ovarian cancer (EOC), including the high-grade serous subtype (HGSC), and expression of individual POTEs correlates with chemoresistance and reduced survival in HGSC. The mechanisms driving POTE overexpression in EOC and other cancers is unknown. Here, we investigated the role of epigenetics in regulating POTE expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 72 publications
0
20
0
Order By: Relevance
“…In addition expression of individual gene in POTE gene family correlated with chemoresistance and poor clinical outcome in HGSOC patients. Furthermore, several epigenetic alternations (pericentromeric activation, global and locus-specific L1 hypomethylation, and locus-specific 5' CpG hypomethylation) served as a determinant for regulation of epigenetic activation of POTE gene (Sharma et al, 2019).…”
Section: Prognosismentioning
confidence: 99%
“…In addition expression of individual gene in POTE gene family correlated with chemoresistance and poor clinical outcome in HGSOC patients. Furthermore, several epigenetic alternations (pericentromeric activation, global and locus-specific L1 hypomethylation, and locus-specific 5' CpG hypomethylation) served as a determinant for regulation of epigenetic activation of POTE gene (Sharma et al, 2019).…”
Section: Prognosismentioning
confidence: 99%
“…In agreement, DNA hypomethylation occurs at repetitive elements (RE), including the interspersed retrotransposon LINE-1 [7], which accounts for~17% of the genome. Global DNA hypomethylation (GDHO) is also associated with hypomethylation and activation of cancer-testis or cancer-germline (CG) genes [8][9][10][11][12][13]. Epigenomic approaches have revealed that GDHO is not random or driven solely by changes at RE, but rather is localized to large genomic regions referred to as hypomethylated blocks [14][15][16].…”
mentioning
confidence: 99%
“…CTAs are normally involved in self-renewal and differentiation of pluripotent and multipotent stem cells, while aberrant expression is associated with cancer transformation and abnormal differentiation of cancer stem cells [ 138 ]. Studies have implicated global and locus-specific DNA hypomethylation as a key mechanism promoting CTA expression in cancer, including epithelial ovarian cancer [ 139 ]. Cancer patients often develop spontaneous immune reactions against CTAs demonstrating their immunogenicity [ 137 ].…”
Section: Cancer and Immune System Interactionsmentioning
confidence: 99%